A novel consensus‐based computational pipeline for screening of antibody therapeutics for efficacy against SARS‐CoV‐2 variants of concern including Omicron variant. Issue 6 (16th January 2023) - Kumar, Naveen; Kaushik, Rahul; Zhang, Kam Y. J.; Uversky, Vladimir N.; Sahu, Upasana; Sood, Richa; Bhatia, Sandeep
Abstract: Multiple severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) variants continue to evolve carrying flexible amino acid substitutions in the spike protein's receptor binding domain (RBD). These substitutions modify the binding of the SARS‐CoV‐2 to human angiotensin‐converting enzyme 2 (hACE2) receptor and have been implicated in altered host fitness, transmissibility, and efficacy against antibody therapeutics and vaccines. Reliably predicting the binding strength of SARS‐CoV‐2 variants RBD to hACE2 receptor and neutralizing antibodies (NAbs) can help assessing their fitness, and rapid deployment of effective antibody therapeutics, respectively. Here, we introduced a two‐step computational framework with 3‐fold validation that first identified dissociation constant as a reliable predictor of binding affinity in hetero‐ dimeric and trimeric protein complexes. The second step implements dissociation constant as descriptor of the binding strengths of SARS‐CoV‐2 variants RBD to hACE2 and NAbs. Then, we examined several variants of concerns (VOCs) such as Alpha, Beta, Gamma, Delta, and Omicron and demonstrated that these VOCs RBD bind to the hACE2 with enhanced affinity. Furthermore, the binding affinity of Omicron variant's RBD was reduced with majority of the RBD‐directed NAbs, which is highly consistent with the experimental neutralization data. By studying the atomic contacts between RBD and NAbs, we revealed the molecular footprints of four NAbs (GH‐12, P2B‐1A1, Asarnow_3D11, and C118)—that may likely neutralize the recently emerged Omicron variant—facilitating enhanced binding affinity. Finally, our findings suggest a computational pathway that could aid researchers identify a range of current NAbs that may be effective against emerging SARS‐CoV‐2 variants.